Virtual Network Embedding: A Hybrid Vertex Mapping Solution for Dynamic Resource Allocation. (2nd September 2012) - Razzaq, Adil; Hidell, Markus; Sjödin, Peter
Abstract : Virtual network embedding (VNE) is a key area in network virtualization, and the overall purpose of VNE is to map virtual networks onto an underlying physical network referred to as a substrate. Typically, the virtual networks have certain demands, such as resource requirements, that need to be satisfied by the mapping process. A virtual network (VN) can be described in terms of vertices (nodes) and edges (links) with certain resource requirements, and, to embed a VN, substrate resources are assigned to these vertices and edges. Substrate networks have finite resources and utilizing them efficiently is an important objective for a VNE method. This paper analyzes two existing vertex mapping approaches—one which only considers if enough node resources are available for the current VN mapping and one which considers to what degree a node already is utilized by existing VN embeddings before doing the vertex mapping. The paper also proposes a new vertex mapping approach which minimizes complete exhaustion of substrate nodes while still providing good overall resource utilization. Experimental results are presented to show under what circumstances the proposed vertex mapping approach can provide superior VN embedding properties compared to the other approaches.